DIVERSI TINDAK PIDANA NARKOTIKA TERHADAP ANAK (Studi Kasus Di Kabupaten Sambas). - ARDHI PRASETYO, S.H NPM.A2021151047, Jurnal Mahasiswa s2 Hukum Untan (Jurnal NESTOR Magister Hukum, 2017)
ABSTRACT This thesis discusses the diversion of narcotics crime against children (Case Study In Sambas District). From the results of this thesis research obtained the conclusion that the Implementation of Diversity Against Children Perpetrators of Narcotics Crime Based on Law Number 11 Year 2012 About Child Criminal Justice System. In the review of the legal position of the diversion of drug abusers of children in the perspective of the development of law pidanamerupakan non-penal policy measures handling criminal child friendly, because handling is diverted from the path of the juvenile justice system. Diversion start from the assumption that the process of the treatment of children through the juvenile justice system is more likely negative than positive for the development of drug abusers anak.Berkaitan with penanganananak, main problems arising from the criminal justice process child or a criminal verdict is stigma attached to convicted drug abuse after Finished criminal justice process. The tendency to increase the abuse of narcotics by children, to encourage efforts to overcome and handling it specifically in the field of child criminal law.Diversion start from the assumption that the process of the treatment of children through the juvenile justice system is more likely negative than positive for the development of drug abusers anak.Berkaitan with penanganananak, main problems arising from the criminal justice process child or a criminal verdict is stigma attached to convicted drug abuse after Finished criminal justice process. The increasing tendency of drug abuse by children, encourages the effort of handling and handling it specifically in the field of child criminal law. Diversi with Restorative Justice approach in its development is a settlement of child crime cases that have been practiced by various countries, including in Indonesia as stipulated in Law no. 11 Year 2012 on the Criminal Justice System of Child and Government Regulation no. 65 The year 2015. The concept of diversion set forth in the Indonesian Criminal Justice System is the obligation to undertake Diversity at every stage of the judicial process (Investigations, Prosecutions and Courts). The arrangement of diversion in the direction of narcotics perpetrators for the future of the implemented diversion concept In Indonesia is only a component of the improvement of the structure of the Criminal Justice System as an alternative to formal criminal justice, by placing Diversity efforts at every stage of the judicial process (Investigation, Prosecution and Courts). The concept of diversion is not much different from the divergence concept applied in Australia, Police Diversion. This is based on the consideration of the Police as the first gate to handle children in conflict with the law to determine whether a child will proceed to the judicial or other informal proceedings such as penal mediation. In relation to the handling of child abuse drug narcotics police as the discretionary authority holder should conduct Diversity through the program Medical rehabilitation and social rehabilitation without being faced with a criminal justice process. Keywords: Diversity, Crime, Narcotics, Children. ABSTRAK Tesis ini membahas tentang diversi tindak pidana narkotika terhadap anak (Studi Kasus Di Kabupaten Sambas). Dari hasil penelitian tesis ini diperoleh kesimpulan bahwa Pelaksanaan Diversi Terhadap Anak Pelaku Tindak Pidana Narkotika Berdasarkan Undang-Undang Nomor 11 Tahun 2012 Tentang Sistem Peradilan Pidana Anak. Di tinjau dari kedudukan hukum diversi terhadap anak penyalahguna narkotika dalam perspektif perkembangan hukum pidanamerupakan langkah kebijakan non-penal penanganan anak pelaku tindak pidana anak, karena penanganannya dialihkan dari jalur sistem peradilan anak. Diversi berangkat dari asumsi bahwa proses penanganan anak lewat sistem peradilan anak lebih besar kemungkinan negatifnya daripada positifnya bagi perkembangan anak.Berkaitan dengan penanganananak penyalahguna narkotika, permasalahan pokok yang ditimbulkan dari proses peradilan pidana anak atau suatu putusan pidana adalah Stigma yang melekat pada terpidana penyalahgunaan narkotika setelah selesai proses peradilan pidana. Kecenderungan meningkatnya penyalahgunaan narkotika yang dilakukan anak, mendorong upaya penanggulangan dan penanganannya secara khusus dalam bidang hukum pidana anak. Diversi dengan pendekatan Restorative Justice dalam perkembangannya merupakan penyelesaian perkara pidana anak yang sudah dipraktekkan oleh berbagai Negara, termasuk di Indonesia yang diatur dalam Undang-Undang No. 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak dan Peraturan Pemerintah No. 65 Tahun 2015. Konsep diversi yang diatur dalam Sistem Peradilan Pidana di Indonesia adalah meletakkan kewajiban untuk melakukan Diversi dalam setiap tahap proses peradilan (penyidikan, Penuntutan dan Pengadilan).Pengaturan diversi terhadap arah pelaku tindak pidana narkotika untuk masa yang akan datang konsep diversi yang dimplementasikan di Indonesia hanyalah sebuah komponen dari perbaikan struktur Sistem Peradilan Pidana Anak sebagai alternatif dari peradilan pidana formal, dengan meletakkan upaya Diversi dalam setiap tahap proses peradilan (penyidikan, Penuntutan dan Pengadilan). Konsep diversi terhadap anak di masa yang akan datang bukan merupakan sebuah program alternatif penanganan anak yang berhadapan dengan hukum semata, tapi diversi yang benar-benar mengeluarkan anak dari proses peradilan pidana. Konsep diversi tersebut tidak jauh berbeda dengan konsep diversi yang diterapkan di Australia yaitu Police Diversion. Hal ini didasarkan pada pertimbangan Polisi sebagai gerbang pertama yang menangani anak yang berkonflik dengan hukum menjadi penentu apakah seorang anak akan dilanjutkan ke proses peradilan atau tindakan informal lainnya seperti mediasi penal.Berkaitan dengan penanganan anak penyalahguna narkotika polisi sebagai pemegang kewenangan diskresi seharusnya melakukan Diversi melalui program rehabilitasi medis dan rehabilitasi sosial tanpa harus dihadapkan dengan proses peradilan pidana. Kata Kunci : Diversi, Tindak Pidana, Narkotika, Anak.